1985
DOI: 10.1080/09553008514551051
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Induced DNA Double-strand Breakage Correlates with Cell Killing after X-irradiation

Abstract: The neutral filter elution technique has been used to examine the relationship between X-ray-induced DNA double-strand breakage (dsb) and lethal lesions. The ratios of the different lesions produced by X-irradiation were varied by irradiation in the presence of different radiomodifiers, and in each case the same linear relationship between lethal lesions and induced DNA dsb was found. This relationship also held for cells given a hyperthermic treatment before irradiation. It is concluded that DNA dsb is probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
88
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(96 citation statements)
references
References 8 publications
7
88
1
Order By: Relevance
“…The present investigation extends these studies, and describes the protective effects of WR-1065 on the radiation induced double-strand DNA breaks and repair using the neutral elution assay (Bradley & Kohn, 1979). This procedure is believed to correlate better with radiation induced cell killing (Hutchinson, 1978;Radford, 1985) but is relatively insensitive and requires extremely high, supra-lethal radiation doses. Recent reports (Tilby, 1984;Evans et al, 1986) have expressed concern that the pH originally suggested for the neutral elution procedure (pH 9.6) may include some single-stranded DNA.…”
Section: Double-strand Break Formationmentioning
confidence: 72%
See 1 more Smart Citation
“…The present investigation extends these studies, and describes the protective effects of WR-1065 on the radiation induced double-strand DNA breaks and repair using the neutral elution assay (Bradley & Kohn, 1979). This procedure is believed to correlate better with radiation induced cell killing (Hutchinson, 1978;Radford, 1985) but is relatively insensitive and requires extremely high, supra-lethal radiation doses. Recent reports (Tilby, 1984;Evans et al, 1986) have expressed concern that the pH originally suggested for the neutral elution procedure (pH 9.6) may include some single-stranded DNA.…”
Section: Double-strand Break Formationmentioning
confidence: 72%
“…In addition, these authors reported that the presence of the protector during repair inhibits strand rejoining in irradiated cells. Double-strand breaks (DSB) are widely believed to be more biologically relevant than SSB, and DSB have been implicated as the critical event in radiation-induced cell killing (Hutchinson, 1978;Radford, 1985;Ward, 1986). The neutral elution technique, developed by Bradley and Kohn (1979) measures DNA DSB.…”
mentioning
confidence: 99%
“…After these complex lesions, DSBs are the most harmful lesions to the cell (Ward, 1975). It has been shown, in rodent cells, that the extent of cell death is directly correlated with the yield of DSB under various X-ray irradiation conditions (Radford, 1985). IR is therefore often used in investigations of the cellular response to DSBs.…”
Section: Dynamics and Heterogeneity Of Dna Damagementioning
confidence: 99%
“…Improperly repaired DSB may result in DNA sequence integrity alterations or to cell death (6)(7)(8)(9)(10)(11). While excessive cell death may lead to embryonic malformations and growth retardation, persisting alterations in DNA may be transmitted to the daughter cells of the embryos thereby increasing the risk for postnatal cancer or genetic diseases.…”
Section: Introductionmentioning
confidence: 99%